The Effects of Leverage, Profitability, and Company Size on Tax Aggressiveness - Imam Hidayat; Reza Aini Ellyana (Universitas Pamulang, 2022)
The goal of this study is to see how much leverage, profitability, and company size have on tax aggressiveness in food and beverage firms listed on the Indonesia Stock Exchange. For the 2016-2020 timeframe, the study sample consisted of 8 food and beverage firms listed on the Indonesia Stock Exchange. The research sample used is 8 food and beverage companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling method used purposive sampling method. The data used is secondary data. The analysis used in this research is multiple linear analysis which is processed using eviews10 program. The results show that leverage and company size variables affect on tax aggrressiveness, while profitability variables have no effect on tax aggressivess. Based on the test of the coefficient of determination (R2) equal to 28,3% of the variable tax aggressiveness can be explained by the variable leverage, profitability, company size while 71,7% are influenced by others variable.